Strategies for internalizing the values of Islamic religious education: implementation and their relation to student character of pancasila in SMPIT Daarut Tauhiid Bandung - Syihabuddin, Syihabuddin (TARBAWY: Indonesian Journal of Islamic Education, 2022)
Abstract. This study aims to formulate the type of strategy that can internalize the values of Islamic Religious Education to junior high school students and to formulate the main and selected types of values to be instilled in students. To achieve this goal, the case study method is used. This research was conducted at SMP Daarut Tauhiid, a school in the city of Bandung, West Java which has a good reputation in the community. The research concludes that the material that is internalized to students is in the form of good and strong characters (BAKU-Baik dan Kuat), namely sincere, honest, brave, humble, and tough. The BAKU character, which is in line with the character of the Pancasila students, is internalized through a strategy that integrates example, monitoring, explanation, and storytelling.